Development of unified college admission system for Philippine state universities and colleges: a data-driven approach to equity and access - Abegail G. Bordios; Sherrie Ann Cananua-Labid; Ariel B. Mabansag; Mae V. Cañal; Jake Boy D. Carboquillo; Ma. Andrea C. Del Rosario (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper presents the development and pilot evaluation of the unified college admission system (UCAS), a centralized and equity-oriented digital platform designed to streamline admissions across Philippine state universities and colleges (SUCs). Anchored on Republic Act No. 10931, UCAS functions as a unified application repository that standardizes admissions data, consolidates applicant records, and enables real-time monitoring of equity target students (ETS) to support fair and transparent access to higher education. The system integrates student-facing and administrative portals that facilitate application submission, institutional coordination, and equity-focused analytics. A pilot evaluation involving student applicants and administrators assessed usability, efficiency, and reliability, yielding consistently positive results across user groups. Findings indicate that UCAS is technically robust, user-centered, and suitable for multi-level admissions governance. Overall, the study demonstrates the potential of a centralized, data-driven admissions platform to complement tuition-free education policies by addressing inequities at the admissions stage.